THE TECHNOLOGY OF POWER OF HISTORICAL CAPITALISM: THE RELATIONSHIP BETWEEN THE LOGIC OF CAPITAL ACCUMULATION AND TERRITORIALISM - Валесян, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article  describes  the main  characteristics and  intrinsic  logic  of  capital accumulation and territorial gains in terms of world-systems analysis. Special attention is paid to the basic strategies of capitalism  over  the  past  five  hundred  years,  the  role  of  capital  accumulation  in  the  formation  of international relations and analyzed  the  function of  international  institutions  in  the modern world-system.